Manajemen Strategis Pendidikan Dalam Menyusun Rencana dan Kebijakan yang Efektif - Bilqis Auliatul Khamima; Agus Imaddudin; Mardiyah Mardiyah (Journal of Innovative and Creativity, 2025)
Islamic education is a learning process that aims to instill Islamic religious, moral, and ethical values ​​in students. The concept of Islamic education that integrates a balance between intellectuality and spirituality, so that students not only understand knowledge academically but also apply it in everyday life in accordance with Islamic values. Educational institutions that produce superior products cannot be separated from strategic management which includes the formulation, planning, implementation and evaluation of decisions taken from several elements that support the achievement of educational goals. However, along with the times, the challenges of globalization, technological developments and social change require Islamic education to be more adaptive and structured in its planning. Therefore, it is important to understand the basic concepts of mature strategic planning governance. This study discusses the basic concepts of the governance of educational unit strategic plans. The method used in this study is a literature study using journals, books and previous research that is relevant to the theme. The results of the study are the importance of strategic management in preparing effective educational unit plans and policies, this article also provides a basic understanding to readers before going further into strategic management in educational units. By reviewing this article, researchers hope to be able to open up the horizons of knowledge for their readers.